Pratiche redazionali nel Regno di Napoli in età aragonese: realtà territoriali a confronto - Giuliana Capriolo (Scrineum Rivista, 2017)
The legislative provisions on notaries issued by the Aragonese sovereigns intended to align the editorial procedures and the admission to the notary profession in the Reign of Sicily citra and ultra Farum, together with the procedures of registration and conservation of notarial documents. However, these procedures were not always equally adopted in all the districts of the Reign. On this regard, the following article presents some samples of notarial registers produced in the Province of Principato Citra, that testify to some unique notarial procedures also comparable with other contemporary evidence from Italy and from the Mediterranean Basin.